Solid waste in construction: management analysis of impacts impacted on the environment (Research, Society and Development, 2022)
This article aims to demonstrate the importance of managing solid waste from civil construction, which over the years has presented major environmental problems that occur mainly due to the enormous amount produced by construction and inadequate disposal. From the elaboration of these laws that aim to protect the environment, several sectors of civil construction have been adopting measures to reduce the effects on the environment in response to the impositions of regulation and society itself, and these actions are manifested in a search for acceptable ends in steps such as recycling, energy reduction and loss reduction. In this context, this work aims to analyze the management of solid waste against the impacts caused to the environment. Faced with this conjecture, this study was carried out through the method of deductive approach, through exploratory research with the use of bibliographic data of a qualitative nature, using the method of documental procedure. According to the results found, it was possible to verify the importance of laws that regulate the proper disposal of solid waste from civil construction and the implementation of practices that help to reduce this waste in the environment. However, despite this effort, the disposal of debris in civil construction still has a lot to progress so that there are significant reductions, thus reducing the impact on the environment, and in this sense, it is necessary that the environmental protection laws be more effective in the inspection so that this disposal is done properly.